Reorganizing governmental industrial classification of disaster and safety industries in Korea: A demand-based approach. (February 2021) - Hwang, Ha; Oh, Yoon-kyung; Kim, Byeong Je; Chung, Ji-Bum
Abstract: The private sector can play a crucial role in enhancing disaster resilience. The industry classification and statistics can provide the basic information needed to understand the landscape of the disaster and safety industry (DSI 1 ). The purpose of this study is to investigate problems in the first supply-based DSI classification (DSIC 2 ) of Korea and suggest a more appropriate demand-based system. A correlation analysis and network cluster analysis were conducted to demonstrate problems of the first DSIC in Korea. The new DSIC was then proposed from a hazard and function-based approach . The effectiveness of the new DSIC from the viewpoints of exhaustiveness and mutual exclusiveness was validated using the Global Clustering Coefficient . The new DSIC is more effective in reducing overlapping industrial activities in industrial divisions. The new DSIC proposed in this study was adopted by the Statistics in Korea in 2018 and is being used as the official DSIC in Korea.